CONSTITUTIONAL FOUNDATIONS OF IDEOLOGICAL PLURALISM IN THE RUSSIAN FEDERATION AND FOREIGN COUNTRIES: A COMPARATIVE LEGAL ASPECT - Nikolay A. Taraban (Сравнительная политика)
The article explores the role of the Constitution in the formation and regulation of the ideology of the state. The Constitution itself is considered in a triune aspect: the Basic Law of the State, the Social Contract and the «Political Code». At the same time, in each of the qualities considered, the task of the Constitution is to ensure the consensus of liberal and social principles, the balance of individualism and solidarity, and reduce the degree of confrontation between different social groups. The author carries out a comparative analysis of the constitutional foundations of ideology in Russia and foreign countries.